Innovation and the Experience with Agricultural Patents Since 1990 Food for Thought - Lippoldt, Douglas C.. (OECD Food, Agriculture and Fisheries Papers, 2015)
This report considers developments in agricultural patents since 1990 and their economic implications. It first provides an overview of the international framework for intellectual property protection and of the general trends in the stringency of protection in OECD countries. It then presents developments in the number of patents originating from OECD and other countries that are granted in Europe and the United States, for all fields and for agriculture and food technologies. These illustrate the leading role played by OECD countries in the provision of successful applications, although non-OECD countries increased their share of the total between 1990 and 2010. Finally, econometric analysis is used to assess the relationships between patenting and selected indicators of innovation and economic performance. The results points to favourable economic developments associated with the patent reforms in the recent decades